Filantropi Buddhis dan Solidaritas Sosial di Kota Kisaran: Kajian Sosiologis - Candra Candra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the phenomenon of fundraising conducted in the name of Buddhism and humanity in Kisaran City, North Sumatra, using a qualitative approach. Data was collected through direct observation, in-depth interviews with the participants, and document analysis related to the fundraising activities that had been conducted. The research findings show that fundraising is carried out in various forms, such as food donations, social activities, and online donations. All of these activities are rooted in Buddhist values, particularly dana (giving) and karuna (compassion). The use of digital technology, especially online donation platforms, has increased community participation and transparency in the fundraising process. However, the study also identified challenges such as the lack of accountability in managing the funds and the risk of misuse that could undermine public trust. In this context, transparency and active community involvement are essential to building trust and ensuring the effectiveness of religious philanthropy. The study concludes that the sustainability of Buddhist fundraising practices in modern society can be achieved by combining spiritual integrity, good governance, and appropriate technology adaptation. Through this holistic approach, Buddhism-based fundraising can remain relevant and effective in supporting humanitarian activities in the digital age.